Performance comparison of ethanol and butanol production in a continuous and closed-circulating fermentation system with membrane bioreactor. Issue 3 (16th March 2017) - Chen, Chunyan; Long, Sihua; Li, Airong; Xiao, Guoqing; Wang, Linyuan; Xiao, Zeyi
ABSTRACT: Since both ethanol and butanol fermentations are urgently developed processes with the biofuel-demand increasing, performance comparison of aerobic ethanol fermentation and anerobic butanol fermentation in a continuous and closed-circulating fermentation (CCCF) system was necessary to achieve their fermentation characteristics and further optimize the fermentation process. Fermentation and pervaporation parameters including the average cell concentration, glucose consumption rate, cumulated production concentration, product flux, and separation factor of ethanol fermentation were 11.45 g/L, 3.70 g/L/h, 655.83 g/L, 378.5 g/m 2 /h, and 4.83, respectively, the corresponding parameters of butanol fermentation were 2.19 g/L, 0.61 g/L/h, 28.03 g/L, 58.56 g/m 2 /h, and 10.62, respectively. Profiles of fermentation and pervaporation parameters indicated that the intensity and efficiency of ethanol fermentation was higher than butanol fermentation, but the stability of butanol fermentation was superior to ethanol fermentation. Although the two fermentation processes had different features, the performance indicated the application prospect of both ethanol and butanol production by the CCCF system.